The Republic of Yemen : Comprehensive Development Review, Environment - World Bank (Washington, DC, 2013)
The review focuses on development and the environment in Yemen, particularly analyzing the environment resource base, where renewable fresh water is scarce, mainly ground water, and its over exploitation is one of the country's major environmental problems. Fisheries resources are also important, while oil and gas are significant resources contributing to some eighty five percent of Yemen's export revenues. Environmental problems are caused fundamentally due to: population growth; poverty; and institutional weaknesses. Main issues discussed include water depletion, pollution and supply; land, and habitat degradation, in addition to soil erosion; and, loss of biodiversity, mostly resulting from poor management of water and eco-tourism. Waste water and solid waste management, including hazardous waste and pesticide management, are outlined as serious environmental problems, requiring immediate appropriate disposal. Priority actions of the national environment action plan identify the need for institutional capacity building regarding environmental management, to include local pilot programs, as well as disaster preparedness at Aden, and Hodeidah ports concerning oil spills. Likewise, the water resources authority should be strengthened, to include the development of water resources information systems, and a comprehensive Water Law. Land use planning should be established to promote land zoning, and registration; a desertification control program should be implemented, and grazing reserves, and pest management techniques promoted. It is suggested waste management would be improved through privatization of solid waste collection, of water treatment, and of disposal of hazardous wastes, while the regulation of hospital waste disposal, should undergo pilot testing.